ANALYSIS OF PATIENT SATISFACTION TOWARDS SERVICE QUALITYOUTPATIENT REGISTRATION IN THE ERA OF ELECTRONIC MEDICAL RECORDS - Syndia Puspitasari (Pedagogic Research-Applied Literacy Journal, 2026)
To improve the quality of hospital quality, it can be seen from patient satisfaction. The quality of quality service can be seen from how patient services are managed, reviewed from the outpatient registration area. Based on the results of initial observations at Hospital "X", several problems were still found, such as unstructured queues, poor communication with patients, and problems in service quality. The purpose of this study was to determine the level of patient satisfaction with the quality of outpatient registration services in the RME era at Hospital "X". This study used a quantitative analytic research method. The population used was outpatients at Hospital "X" with a sample size of 98 respondents. The results of the study using the chi-square test (p-value 0.001 <0.05) showed that there was a significant relationship between patient satisfaction and the quality of registration services at Hospital "X". With this study, it is hoped that the Hospital can continue to improve and maintain the quality of services at the outpatient registration area.